2020
DOI: 10.3389/fphar.2020.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Herbarium Collections to the Discovery of Novel Treatments for Alzheimer’s Disease, a Case Made With the Genus Eriodictyon

Abstract: Plants, in particular those with a history in traditional medicine, hold enormous potential as sources of new therapies for dementias such as Alzheimer's disease (AD). The largest collections of plants can be found in herbaria all over the world, but the value of these collections to AD drug discovery has been significantly neglected. As a proof of principle, we investigated the neuroprotective activity of herbarium specimens of Eriodictyon (yerba santa), a genus with a long history of usage by the indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Yerba santa is a plant that has been brewed into a tea and used as a bitter flavoring additive to foods historically by Native Americans [ 126 ]. Previous studies have demonstrated that sterubin extracted from Yerba santa exhibited strong neuroprotective properties and held notable potential as a neuroprotectant [ 127 , 128 ]. Recently, scientists found that sterubin is an effective iron chelator, which could inhibit ferroptosis in a dose-dependent way through increasing GSH, decreasing ROS levels and activating Nrf2/ATF4 signaling pathway in glutamate-treated HT22 cells [ 129 ].…”
Section: Natural Bioactive Compounds As Ferroptosis Regulatorsmentioning
confidence: 99%
“…Yerba santa is a plant that has been brewed into a tea and used as a bitter flavoring additive to foods historically by Native Americans [ 126 ]. Previous studies have demonstrated that sterubin extracted from Yerba santa exhibited strong neuroprotective properties and held notable potential as a neuroprotectant [ 127 , 128 ]. Recently, scientists found that sterubin is an effective iron chelator, which could inhibit ferroptosis in a dose-dependent way through increasing GSH, decreasing ROS levels and activating Nrf2/ATF4 signaling pathway in glutamate-treated HT22 cells [ 129 ].…”
Section: Natural Bioactive Compounds As Ferroptosis Regulatorsmentioning
confidence: 99%
“…Because our focus is on oxytosis/ferroptosis, we use a phenotypic screening assay that exposes cultured nerve cells to chemical inducers of oxytosis/ferroptosis (glutamate, erastin and RSL3) (Maher et al, 2020). We have shown that this assay is not only good at identifying natural inhibitors of oxytosis/ferroptosis but can also be used to screen extracts from plants with ethnopharmacological value and identify the underlying active agents (Currais, Chiruta, et al, 2014; Fischer et al, 2019; Maher, Fischer, et al, 2020). The assay also has the advantages of being simple, quick, of relatively low cost and high throughput, which significantly minimizes the unnecessary killing of animals.…”
Section: Identifying Anti‐oxytotic/ferroptotic Compounds From Plantsmentioning
confidence: 99%
“…Various methods to screen plant extracts and identify biologically active compounds have been used. A step-wise approach to identifying novel anti-oxytotic/ferroptotic neuroprotective compounds from plants is described below based on our own experience in successfully developing AD drug candidates as well as on the published literature (Atanasov et al, 2015;Azmir et al, 2013;Currais et al, 2018Currais et al, , 2019Currais, Chiruta, et al, 2014;Currais, Prior, et al, 2014;Fischer et al, 2019;Maher, Fischer, et al, 2020) (Figure 3) (for more details, please see an excellent review from Atanasov et al, 2015).…”
Section: Oxytosis/ferroptosis and Redox Regulation In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products have been used in traditional medicine and are gaining increased attention for their potential as neuroprotectants interfering with disease progression. The well-established antioxidant features of natural products, i.e., their radical scavenging abilities, are important for neuroprotection induced by oxidative stress . However, polyphenols as plant secondary metabolites have also shown to be neuroprotective by activating several intracellular pathways in addition to their antioxidative features .…”
Section: Introductionmentioning
confidence: 99%